Structural Dynamics of the Lipid Antigen-Binding Site of CD1d Protein - Bruno Cuevas-Zuviría; Marina Mínguez-Toral; Araceli Díaz-Perales; María Garrido-Arandia; Luis F. Pacios (Biomolecules, 2020)
CD1 molecules present lipid antigens to T-cells in early stages of immune responses. Whereas CD1‒lipid‒T-cell receptors interactions are reasonably understood, molecular details on initial trafficking and loading of lipids onto CD1 proteins are less complete. We present a molecular dynamics (MD) study of human CD1d, the isotype that activates iNKT cells. MD simulations and calculations of properties and Poisson-Boltzmann electrostatic potentials were used to explore the dynamics of the antigen-binding domain of the apo-form, CD1d complexes with three lipid–antigens that activate iNKT cells and CD1d complex with GM2AP, a protein that assists lipid loading onto CD1 molecules in endosomes/lysosomes. The study was done at pH 7 and 4.5, values representative of strongly acidic environments in endosomal compartments. Our findings revealed dynamic features of the entrance to the hydrophobic channels of CD1d modulated by two α helices with sensitivity to the type of lipid. We also found lipid- and pH-dependent dynamic changes in three exposed tryptophans unique to CD1d among the five human CD1 isotypes. On the basis of modelled structures, our data also revealed external effects produced by the helper protein GM2AP only when it interacts in its open form, thus suggesting that the own assistant protein also adapts conformation to association with CD1d.